Zurich Consensus: Statement of German Experts on St. Gallen Conference 2011 on Primary Breast Cancer (Zurich 2011) - Untch, Michael; Gerber, Bernd; Möbus, Volker; Schneeweiss, Andreas; Thomssen, Christoph; Minckwitz, Gunter von; Beckmann, Matthias Wilhelm; Blohmer, Jens-Uwe; Costa, Serban-Dan; Diedrich, Klaus; Diel, Ingo J.; Eiermann, Wolfgang; et al. (Breast care, 2011)
Every 2 years, the International Consensus Conference on the Treatment of Primary Breast Cancer takes place in St. Gallen. Given that the concept of the St. Gallen Consensus Conference mainly reflects an international opinion, it appears useful to adapt the results of the vote for everyday therapy in Germany. A German working group comprising 28 breast cancer experts, amongst whom there are 3 members of the international St. Gallen panel, has therefore commented on this year’s St. Gallen Consensus Conference (2011) from the German viewpoint. The focus of interest of this year’s St. Gallen Conference was tumour biology as the starting point for decisions regarding individual therapy. There was an intensive discussion in relation to the clinical relevance of predictive and prognostic factors and possible consequences for decisions regarding therapy. Therefore, questions concerning the indication for adjuvant chemotherapy focused especially on the significance of the molecular phenotype of the tumour. In addition, important points for discussion were also the value of complete axillary dissection and the use of accelerated complete breast irradiation.